Spatiotemporal Analysis of B-Value at Mount Slamet (2014–2023) - Ika Maulita; Sugito Sugito; Lusia Silfia Pulo Boli (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2024)
This study investigates the spatial and temporal distribution of b-values at Mount Slamet, one of Indonesia’s most active volcanoes, during its eruption activities from 2014 to 2023. The primary objective is to explore how variations in b-values correlate with stress conditions and volcanic activity, providing insights into eruption forecasting. Seismic data were sourced from USGS, BMKG, and local networks and analyzed using ZMAP and MATLAB to calculate b-values, assess magnitude completeness, and perform spatial and temporal analyses. Results reveal notable spatial variability: higher b-values in the northern and northeastern regions indicate lower stress levels, while lower b-values in the southwestern region suggest elevated stress concentrations. These spatial patterns align with geological features, highlighting zones of intense tectonic and magmatic interactions. Temporally, b-values consistently declined before major eruptions in 2017 and 2020, reflecting increased stress and larger seismic events. Post-eruption, b-values rose, indicating stress reduction and stabilization of the volcanic system. These findings underscore the value of b-value monitoring as an effective tool for eruption forecasting. The observed spatial and temporal trends offer critical insights into Mount Slamet’s evolving stress conditions, aiding disaster preparedness and risk mitigation strategies for local communities. The study highlights the importance of continuous seismic monitoring combined with advanced analytical techniques to enhance the predictive capabilities of volcanic hazard assessments. Future research should integrate additional geophysical parameters, refine predictive models, and extend analyses to similar volcanic settings to improve global understanding of volcanic processes and enhance early warning systems.